Field Inter-Rater Reliability of the Psychopathy Checklist-Revised - Ismail, Ghena (International journal of offender therapy and comparative criminology, 2018)
Strong inter-rater reliability has been established for the Hare Psychopathy Checklist-Revised (PCL-R), specifically by examiners in research contexts. However, there is less support for inter-reliability in applied settings. This study examined archival data that included a sample of sex offenders (n = 178) who entered federal custody between 1992 and 1998. The offenders were assessed using the PCL-R on two occasions. The first assessment occurred at Millhaven Institution, the intake unit for federally incarcerated offenders in the province of Ontario. The second assessment took place upon inmates’ transfer to the Regional Treatment Center, which admits federal inmates with intense psychological and psychiatric needs. Intra-class correlation coefficients (ICCs) were calculated for item, total, factor, and facet scores. The ICC absolute agreement for the PCL-R total and factor scores from raters across both settings was slightly better than what has been previously reported by Hare. Results of this study show that the reliability of PCL-R scores in field settings can be comparable to those in research settings. Authors conclude by highlighting the importance of training, consultation, considering different scores for a given item, following the guidelines of the manual in addition to considering measures that enhance neutrality and reliability of findings in the criminal justice system.